Bacillary Angiomatosis in an HIV-positive Man with Multiple Risk Factors: A Clinical and Epidemiological Puzzle - Farrah J Mateen; Jill C Newstead; Karen L McClean (Canadian Journal of Infectious Diseases and Medical Microbiology)
A 36-year-old man with advanced AIDS presented with skin lesions, fever and weight loss. Physical examination revealed skin lesions suggestive of bacillary angiomatosis. Diagnostic imaging identified bone lesions, soft tissue masses and a single hepatic lesion. His clinical presentation was most consistent with Bartonella quintana; however, his risk for infection with B quintana was limited to a remote, brief period of homelessness. In contrast, his frequent contact with cats presented substantial potential exposure to Bartonella henselae. Diagnosing a Bartonella infection presents challenges. The detection of bacteremia is hindered by slow growth in BACTEC media (BD Diagnostic Systems, Canada). In the present case, recovery of the organism required blind subcultures after at least eight days of incubation. Speciation by 16s ribosomal RNA analysis confirmed B quintana as the pathogen. Because the patient presented with skin lesions, the diagnosis was straightforward; however, skin lesions are nondiagnostic in some cases. Microbiological confirmation of the diagnosis rests on sufficient clinical suspicion to apply labour-intensive laboratory protocols.